Investigation on characteristic length testing methods for failure prediction of composite multi-bolt joints. (April 2015) - Zhang, Jianyu; Liu, Fengrui; Zhao, Libin; Shan, Meijuan
Characteristic lengths (CLs) are key factors in the characteristic curve method (CCM), which is widely used in engineering to predict the failure of composite multi-bolt joints. They directly affect the accuracy of predicting the joint failure. To identify suitable CL testing methods, six schemes have been designed and tested, in which two tensile CL specimens (open- and filled-hole laminates) and three compressive CL specimens (semi-circular notch laminates, pin-loaded hole laminates and single-bolt joints) have been compiled. Additionally, 3D FE analyses on the stress concentration have been performed and a discussion of the unit failure index curves of different specimens has been carried out to explore their load-carrying mechanism and determine why they result in different CLs. Failure predictions of composite multi-bolt joints by using the CCM with different CL testing schemes have been compared and evaluated using related static tensile experimental results. Filled-hole laminates for the tensile CL and single-bolt joints for the compressive CL are recommended because they best approximate the actual structure and obtain accurate failure predictions for composite multi-bolt joints.